Psychological well-being, coping strategies and social support to informal caregivers - Felipe E. García; Universidad Santo Tomás; Esteban Manquián; Universidad de Las Américas; Gisela Rivas; Universidad de Las Américas (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2016)
The purpose of this study was to assess the influence that coping strategies and social support have on the psychological sense of well-being of informal caregivers in the province of Concepción, Chile. We surveyed one hundred and ninety-four people with ages between eighteen to seventy-eight years old. Thirty-one of them (67.3%) were women and sixty-three (32.5%) were men. We used the Brief COPE inventory to evaluate coping strategies, Diener's Fourishing Scale to evaluate the psychological sense of well-being, the Multidimensional Scale of Perceived Social Support (MSPSS) to evaluate the perceived social support, plus a socio-demographic questionnaire. We found a significant correlation between the planning and coping strategies and the perceived social support vs. the sense of psychological well-being. Support by friends turned out to be the only significant predictor of psychological well-being. Among coping strategies, acceptance was the only significant predictor. Social support turned out to be a full mediator between acceptance and the sense of psychological well-being. These results reinforce the importance of social support, not only to reduce the level of discomfort among caregivers, but also to promote their well-being.